PARTISIPASI MASYARAKAT DALAM MEWUJUDKAN PEMBANGUNAN DESA BERKELANJUTAN PADA KELURAHAN KARANGPAWITAN - Eva Agus Triana; Hasfirullah Syaban Bashar; Mohamad Bintang Ramadhan; Evi Priyanti (Journal Publicuho, 2021)
Based on the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia Number 13 of 2020 concerning Priorities for the Use of Village Funds in 2021, SDG's Desa contains 18 development visions that are adapted to the customary conditions of each village. In realizing this vision, one of the obstacles to be overcome is the lack of community participation. This is also experienced by the Karangpawitan Village in Karawang Regency.   The method used in this research is descriptive analysis method using a qualitative approach. The results showed that since the end of 2019, community participation began to grow and resulted in development programs such as the Waste Bank and BSF Maggot Farm Greenday. The program is supported by the active role of the Karangpawitan sub-district government to the maximum so that it has succeeded in massively increasing community participation while producing various benefits.